Comparison of the potentiating effect of variable load jump squats on acute drop jump performance in rugby sevens athletes - Poulos, N.; Haff, G. G.; Nibali, M.; Graham-Smith, P.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2023)
The effect of variable load jump squats (JSs) on acute drop jump (DJ) performance across multiple sets was examined. Seventeen elite rugby sevens athletes performed 3 DJs after 3 repetitions of a JS conditioning activity (CA) performed at 30 or 50% 1RM back squat loads. Acute postactivation performance enhancement (PAPE) in DJ kinetic and kinematic variables was assessed using a commercially available force platform (1,000 Hz). Postactivation performance enhancement was predominant after the 30% 1RM load with the greatest frequency of potentiation exhibited in set 3. The 50% 1RM CA resulted in substantial decrements in DJ performance with the exception of active stiffness, reactive strength index (flight:contact time), and contact time. Moderate differences were observed between the 50 and 30% 1RM loads for peak power (W), impulse (N·s), and force at zero velocity (N); active stiffness was the only variable where PAPE was greater in the 50% 1RM CA (ES: small). Active stiffness was the only variable to display favorable associations with relative strength in both the JS 30% 1RM (ES: 0.38 ± 0.20; moderate) and 50% 1RM (ES: 0.24 ± 0.23; small) CA loads. The JS 30% 1RM CA results in greater magnitude and frequency of PAPE of DJ kinetic and kinematic variables and is recommended if seeking to target PAPE in a range of DJ performance variables. Heavier JS loads may be appropriate if enhancement of muscle stiffness and stretch-shortening cycle efficiency is required. Consideration of targeted kinetic and kinematic variables when selecting CA intensity in complex training design is recommended.